Computer model of accounting of the scientific activity of the education system - Афанасьєва, Христина Олександрівна; Мороз, Ольга Юріївна; Толстолузька, Олена Геннадіївна (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2019)
The work is devoted to the review and analysis of resources of scientific information, the study of the possibilities of developing additional information arrays based on existing sources of scientific and scientometric information. As part of the work, proposed approaches for storing scientometric information, methods for obtaining data which will optimize the time of working with information and require less resources for the implementation of the search for scientific information and its subsequent processing. The result of the work is a computer model that provides the ability to store scientific information in the database, as well as the use of various functions as a database administrator and user rights through the developed C++ client. The proposed model of accounting for scientific activity has the following functional capabilities of software modules: introduction of new and removal of outdated information into a database; submitting information based on some criteria. The architecture of a computer model consists of such software modules as the user role definition module, the database administrator module, and the user module. The model works with information arrays, which are formed on the basis of resources and contain bibliometric and scientometric information and can act as parameters that be able to influence decision making and expand the range of possible cooperation of scientists. The application of the developed computer model allows organizing a flexible search for scientific information in the field of education.